ChemInform Abstract: Formation of Gas‐Phase Peptide Ions and Their Dissociation in MALDI: Insights from Kinetic and Ion Yield Studies. Issue 38 (3rd September 2015) - Moon, Jeong Hee; Yoon, Sohee; Bae, Yong Jin; Kim, Myung Soo
Abstract Review: 130 refs.